Exploring relationships in a university internship program a stakeholder framework for designing and directing effective marketing internships - Hoyle, Jeffrey A. (Scholars' Press, 2014)
The literature reviewed for this study generally supports the perspective that the undergraduate internship experience, for the most part, is doing what it is intended to do by providing actual situations to apply what students have learned in the classroom to the workplace. However, the very nature of public universities, funded by citizens for the greater good of society, working with private corporations, working for stockholders, customers, and other corporate entities looking to maximize returns on their investments, represents challenges for internship directors and student interns. -- Back Cover.